ANALYSIS OF SINGLE NUCLEOTIDE POLYMORPHISMS OF GENES IL17A AND TLR2 IN PATIENTS WITH PERIODONTITIS - Pyndus, V.B.; Dorosh, I.V.; Dienha, O.V.; Litovkin, K.V.; Shnaider, S.A.; Novikova, M.A.; Suslova, О.V. (World of Medicine and Biology, 2022)
The study is devoted to finding the association of single-nucleotide polymorphisms of the IL17A gene and the TLR2 gene with periodontitis in the Ukrainian population. 34 patients participated in the research. They were divided into 2 groups (the study group, which included 22 patients with periodontitis of various degrees of severity; the control group, which included 12 healthy individuals). The dental examination was carried out in a dental office. As a result of the research, it was established that the rs2275913 polymorphism was associated with the risk of periodontitis in the allelic model and the dominant model. The experimental and control groups did not differ significantly in the frequency distribution of genotypes and alleles of the rs5743708 TLR2 G>A (Arg753Gln) polymorphism.
Keywords: oral health; genotyping; interleukin-17A; mediator of immune response